Cream-Skimming or Profit-Sharing? The Curious Role of Purchased Order Flow. - Easley, David; Kiefer, Nicholas M; O'Hara, Maureen (Journal of Finance, 1996)
Purchased order flow refers to the practice of dealers or trading locales paying brokers for retail order flow. It is alleged that such agreements are used to 'cream skim' uninformed liquidity trades, leaving the information-based trades to established markets. We develop a test of this hypothesis, using a model of the stochastic process of trades. We then estimate the model for a sample of stocks known to be used in order purchase agreements that trade on the New York Stock Exchange (NYSE) and the Cincinnati Stock Exchange. Our main empirical result is that there is a significant difference in the information content of orders executed in New York and Cincinnati, and that this difference is consistent with cream-skimming.